Stakeholder perspectives on hiring teaching-focused faculty at research-intensive universities - Ashley N. Harlow; Natascha T. Buswell; Stanley M. Lo; Brian K. Sato (SpringerOpen, 2022)
Abstract Background Teaching-focused faculty positions have grown in popularity in higher education and provide novel opportunities to transform undergraduate science, technology, engineering, and mathematics (STEM) education. The University of California (UC) system employs a unique teaching-focused faculty position, officially called the Lecturer with Potential Security of Employment (L(P)SOE), with the working title called Professor of Teaching (PoT). The UC PoT position is a tenure-track position with teaching as the primary tenure expectation. We present findings from interviews with stakeholder faculty in STEM departments at three UC campuses to identify reasons for hiring PoT, capture accomplishments of PoT in their departments and disciplinary fields, and identify potential barriers to PoT success. Results Overall, this study highlights stakeholder's perspectives on the value of teaching-focused faculty in research-intensive universities. Stakeholders described the goals for hiring Professors of Teaching, which included easing the burden of teaching responsibilities of the departments and adding consistency of instruction. While the stakeholders expressed that PoT were meeting the goals for being hired, they also identified many barriers for PoT being fully integrated and successful. The stakeholders expressed concern about unclear and unfair expectations related to tenure and promotion. Conclusions The findings point to a general undervaluing and underappreciation of teaching-focused faculty and suggest that in order for PoT to have a positive impact on STEM higher education, they need more support and inclusion from their colleagues and institutions.